Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-101
|View full text |Cite
|
Sign up to set email alerts
|

Brief training with rhythmic beat gestures helps L2 pronunciation in a reading aloud task

Abstract: The aim of this study is to assess whether a brief training with rhythmic beat gestures helps L2 pronunciation in a reading aloud task with high school students. In a between-subjects pretest-posttest design, a total of 59 high school students were randomly assigned to one of the following two conditions: the beat gesture group and no-beat gesture group. In the beat gesture condition they were asked to first read two short stories aloud without any gestural instruction (pretest) and in the following two texts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Second, we expect the same positive effects on narrative fluency scores, as previous literature has highlighted the positive effects of producing beat gestures on lexical access in adults (Lucero, Zaharchuk, & Casasanto, 2014), as well as on oral fluency (Rauscher, Krauss, & Chen, 1996) and L2 pronunciation (e.g. Gluhareva & Prieto, 2017;Llanes-Coromina, Prieto, & Rohrer, 2018). Our hypothesis is that the rhythmic properties of beat gestures and their tight synchrony with prominent prosodic positions in speech (Shattuck-Hufnagel & Ren, 2018;McNeill, 1992; see also Esteve-Gibert & Prieto, 2013) can enhance oral speech fluency.…”
Section: The Current Studymentioning
confidence: 62%
“…Second, we expect the same positive effects on narrative fluency scores, as previous literature has highlighted the positive effects of producing beat gestures on lexical access in adults (Lucero, Zaharchuk, & Casasanto, 2014), as well as on oral fluency (Rauscher, Krauss, & Chen, 1996) and L2 pronunciation (e.g. Gluhareva & Prieto, 2017;Llanes-Coromina, Prieto, & Rohrer, 2018). Our hypothesis is that the rhythmic properties of beat gestures and their tight synchrony with prominent prosodic positions in speech (Shattuck-Hufnagel & Ren, 2018;McNeill, 1992; see also Esteve-Gibert & Prieto, 2013) can enhance oral speech fluency.…”
Section: The Current Studymentioning
confidence: 62%
“…Although language rhythm is commonly associated with suprasegmental features, studies have also suggested links between rhythm and segmental phonology, particularly relating to the temporal aspects of the tense-lax contrast in English (Schwartz, 2010). Indeed, rhythmic perception can have an important role in successful language acquisition (Jusczyk, 1999) and practicing musical rhythm can help achieve more native-like pronunciation and fluency (Llanes-Coromina et al, 2018). Former studies also confirmed the existence of shared neurocognitive resources for rhythm in music and speech (e.g., Magne et al, 2016), as well as successful use of musical rhythm in teaching L2 English prosody, particularly in practicing duration contrasts between stressed and unstressed syllables (Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Vilà-Giménez, Igualada, and Prieto (2019) showed that observing storytellers who use beat gestures while telling a story improves the performance of children's narrative abilities in story retelling. Moreover, Llanes-Coromina, Prieto, and Rohrer (2018) showed that asking Catalan speakers to produce beat gestures while reading in L2 in a training phase can benefit fluency in a posttest reading task, when no instructions to gesture are provided. These studies together point toward a positive effect of encouraging the use of gestures on speech fluency, though the speech that was evaluated in terms of fluency was not produced specifically in the encouraging gesture phase, but in a posttest phase.…”
mentioning
confidence: 99%